Changes in arterial function in a mouse model of human familial hypercholesterolaemia. (24th March 2014) - Brinkmann, O.; Schmerbach, K.; Tietge, U. J. F.; Dietrich, T.; Guski, H.; Linz, D.; Kühn, H.; Patzak, A.; Wilfert, K.
Abstract Aim Atherosclerosis is the most common cause of cardiovascular disease. The ApoB mouse is a model for human familial hypercholesterolaemia and has a lipoprotein profile similar to that of humans with atherosclerosis. Therefore, it is a suitable model to investigate the changes in vasoreactivity during atherogenesis. This study investigates contractile and dilatative properties of arteries in this model in relation to age. Methods Male ApoB mice and B6, wild‐type (WT), mice were examined at age four or 18 months. Isometric measurements of 2‐mm ring preparations of the aorta thoracica were performed using a wire myograph. Histological and biochemical methods served to determine atherosclerosis, lipid status and endothelial markers respectively. Results Morphometric analysis showed that all old ApoB mice had severe atherosclerosis in the aorta. Atherosclerotic alteration of the aorta of the ApoB mice coincided with a diminished vasodilatation to acetylcholine. The phenylephrine response was significantly attenuated already to the same degree in the non‐atherosclerotic aorta of the young ApoB mice as in the atherosclerotic aorta of the older ApoB mice. Serum parameters showed a rise in total cholesterol and triglycerides in the ApoB strain compared to WT mice. Soluble intercellular adhesion molecule (sICAM)‐1 and soluble vascular adhesion molecule (sVCAM)‐1 were increased in old compared to young ApoB mice. Conclusion The study shows that reduced acetylcholine‐induced dilatation is related to the presence of atherosclerosis in old ApoB mice. Remarkably, the impaired vessel reactivity to phenylephrine already in young ApoB mice indicates early changes in vascular function in this model.